Sporulation: A response to starvation in the fission yeast Schizosaccharomyces pombe. Issue 3 (21st June 2022) - Ohtsuka, Hokuto; Imada, Kazuki; Shimasaki, Takafumi; Aiba, Hirofumi
Abstract: The fission yeast Schizosaccharomyces pombe employs two main strategies to adapt to the environment and survive when starved for nutrients. The strategies employ sporulation via sexual differentiation and extension of the chronological lifespan. When a cell is exposed to nutrient starvation in the presence of a cell of the opposite sex, the cells undergo fusion through conjugation and sporulation through meiosis. S. pombe spores are highly resistant to diverse stresses and may survive for a very long time. In this minireview, among the various sexual differentiation processes induced by starvation, we focused on and summarized the findings of the molecular mechanisms of spore formation in fission yeast. Furthermore, comparative measurements of the chronological lifespan of stationary phase cells and G0 cells and the survival period of spore cells revealed that the spore cells survived for a long period, indicating the presence of an effective mechanism for survival. Currently, many molecules involved in sporulation and their functions are being discovered; however, our understanding of these is not complete. Further understanding of spores may not only deepen our comprehension of sexual differentiation but may also provide hints for sustaining life. Abstract : The fission yeast, Schizosaccharomyces pombe, employs two main strategies to adapt to the environment and survive when starved for nutrients: chronological lifespan extension and sporulation. In this minireview, we summarize several findings on spore formation in S. pombe . As observed, comparative measurements of the chronological lifespan of the stationary phase and the survival period of spore cells revealed that the latter achieved an extremely long survival period.